2006
DOI: 10.1016/j.exer.2006.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the methionine sulfoxide reductase A gene results in loss of mitochondrial membrane potential and increased ROS production in human lens cells

Abstract: Accumulation of methionine sulfoxide (Met(O)) is a significant feature of human cataract and previous studies have shown that methionine sulfoxide reductase A (MsrA), which acts to repair Met (O), can defend human lens cells against oxidative stress induced cell death. A key feature of oxidative stress is increased reactive oxygen species (ROS) in association with loss of mitochondrial function. Here, we sought to establish a potential role for MsrA in the accumulation of ROS in lens cells and the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 23 publications
(28 reference statements)
4
65
0
Order By: Relevance
“…Viability in this work was measured using the MTS assay which measures the activity of mitochondrial enzymes indicating that MsrA is important in protecting mitochondrial function in the lens cell. Marchetti et al, (2006) carried out further studies on the effect of silencing the MsrA gene. They showed that decreased MsrA levels not only reduced cell viability but also allowed increased ROS production in the cell and a decrease in mitochondrial membrane potential even in the absence of oxidative stress, these effects were augmented by TBHP-induced oxidative stress.…”
Section: The Methionine Sulfoxide Reductase Repair Systemmentioning
confidence: 99%
“…Viability in this work was measured using the MTS assay which measures the activity of mitochondrial enzymes indicating that MsrA is important in protecting mitochondrial function in the lens cell. Marchetti et al, (2006) carried out further studies on the effect of silencing the MsrA gene. They showed that decreased MsrA levels not only reduced cell viability but also allowed increased ROS production in the cell and a decrease in mitochondrial membrane potential even in the absence of oxidative stress, these effects were augmented by TBHP-induced oxidative stress.…”
Section: The Methionine Sulfoxide Reductase Repair Systemmentioning
confidence: 99%
“…Bacteria grow well when methionine is replaced by its carbon-containing analogue, norleucine, but the cells are much more susceptible to killing by oxidative stresses (3). Several investigations demonstrated that modulation of MsrA activity altered the level of reactive oxygen species; overexpression lowered the level in PC-12 cells (13), whereas lens cells lacking MsrA had an increased level (14). Increased expression of either MsrA in WI-38 fibroblasts or MsrB in MOLT-4 leukemia cells reduced the steady state level of oxidized proteins after a hydrogen peroxide challenge (15,16).…”
mentioning
confidence: 99%
“…In contrast, knocking out MsrA makes mammalian cells more sensitive to oxidative stress. MsrA and MsrB knockout in lens and retinal cells make these cells more sensitive to oxidation (Marchetti et al, 2006;Kantorow et al, 2004). There have been reports on MsrA knockout mice in which it is clear that these animals are very sensitive to increased oxygen tension, although there is conflicting data on their life span and the presence of a neurological defect (Moskovitz et al, 2001, Salmon et al, 2009).…”
Section: Msra and Cellular Protectionmentioning
confidence: 99%
“…There are now several cell culture studies to support this mechanism. In PC12 cells over-expression of MsrA lowers the level of ROS in the cells and in lens and retinal cells knocking out of MsrA leads to higher ROS levels (Yermolaieva et al, 2004;Marchetti et al, 2006).…”
Section: Dual Function Of the Msr Systemmentioning
confidence: 99%